2010
DOI: 10.1258/acb.2010.010197
|View full text |Cite
|
Sign up to set email alerts
|

Probabilistic Bayesian reasoning can help identifying potentially wrong immunoassays results in clinical practice: even when they appear ‘not-unreasonable’

Abstract: Background: Immunoassays are susceptible to analytical interferences including from endogenous immunoglobulin antibodies at a rate of 0.4% to 4%. Hundreds of millions of immunoassay tests (.10 millions in the UK alone) are performed yearly worldwide for measurements of an array of large and small moieties such as proteins, hormones, tumour markers, rheumatoid factor, troponin, small peptides, steroids and drugs. Methods: Interference in these tests can lead to false results which when suspected, or surmised, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 56 publications
2
12
0
Order By: Relevance
“…Supporting this finding, our previous study showed that the decline in the rates of HBsAg signal/cut-off values was not associated with the serum RF concentration in an HBsAg ELISA [5]. Furthermore, our previous and present studies provided evidence that other important aspects such as binding affinity/avidity of RF affected the pattern and degree of interference in immunoassays [21]. It has been reported that RF leads to a false-positive or higher results in immunoassays [7][10].…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…Supporting this finding, our previous study showed that the decline in the rates of HBsAg signal/cut-off values was not associated with the serum RF concentration in an HBsAg ELISA [5]. Furthermore, our previous and present studies provided evidence that other important aspects such as binding affinity/avidity of RF affected the pattern and degree of interference in immunoassays [21]. It has been reported that RF leads to a false-positive or higher results in immunoassays [7][10].…”
Section: Discussionsupporting
confidence: 84%
“…These data supported our suspicion that RF causes a negative interference in BNP CMIA. The probability of a negative interference rate from RF assuming a prevalence of heart failure of 80% in symptomatic patients was calculated to be 33% according to Bayes theorem [21]), a figure not dissimilar to ∼50% found in this study. Therefore, in order to determinate BNP level in RF-positive plasma samples with better accuracy, we suggest that samples need to be pretreated with commercially available blocking reagents such as heterophil-blocking reagent [17], [21].…”
Section: Discussionsupporting
confidence: 38%
See 1 more Smart Citation
“…To identify samples, Ismail et al (25) suggest a probabilistic approach, i.e., elevated results in assays known to have a low rate of true positive results should be retested for interference. We agree with this probabilistic approach, but we also think that the impact of the assay result should guide which samples to retest for interference.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, Ismail et al . [23] estimated that the probability of a raised TSH result in a young adult being a false positive is greater than 30%.…”
Section: Resultsmentioning
confidence: 99%